2010
DOI: 10.1111/j.1754-4505.2010.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

ARTICLE: Recruitment of rural and cognitively impaired older adults for dental research

Abstract: The recruitment of community-dwelling older adults, particularly those with cognitive impairment and those residing in rural areas, has been consistently challenging for researchers, especially in the dental field. This study reports on recruitment experiences from an ongoing study investigating the association between oral health and cognitive status in later life. Multiple recruitment strategies, including educational presentations and traveling to participants’ homes, were used to enroll rural elderly parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Cognitive study participants were selected based on: 1) age 70 years and older, 2) resident of West Virginia, 3) community-living, and 4) dentate (having at least four natural teeth). Oral evaluations were performed by calibrated researchers using guidelines and protocols from the National Health and Nutrition Examination Survey (NHANES IV) [ 13 ]. Subgingival plaque samples were collected using sterile periodontal curettes from six sites as follows: the buccal surface of the most anterior molar in each quadrant, and the buccal surface of #11 and #31.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive study participants were selected based on: 1) age 70 years and older, 2) resident of West Virginia, 3) community-living, and 4) dentate (having at least four natural teeth). Oral evaluations were performed by calibrated researchers using guidelines and protocols from the National Health and Nutrition Examination Survey (NHANES IV) [ 13 ]. Subgingival plaque samples were collected using sterile periodontal curettes from six sites as follows: the buccal surface of the most anterior molar in each quadrant, and the buccal surface of #11 and #31.…”
Section: Methodsmentioning
confidence: 99%
“…Using an Illumina HiSeq1000 DNA sequencer and a sample preparation and analysis pipeline that enabled multiple samples to be sequenced within the same sequencing lane, we were able to generate and analyze economically more than one million bacterial DNA sequences from each of 15 subgingival plaque samples. The participants were enrolled in a study that assessed oral health and cognitive function among adults at least 70 years old from West Virginia, some of whom were from medically underserved communities [ 20 ]. These sequences were analyzed using bioinformatics tools available in the publicly accessable software package Quantitative Insights into Microbial Ecology (QIIME) [ 21 ], and sequence comparisons were made among participants who were clinically assessed as normal or exhibited alterations in cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…This proved to be very difficult especially among the community dwellers. Studies have reported on the difficulties that are at times encountered when recruiting elderly community dwellers (Wu et al 2010;Kammerer et al 2019). Four dental examiners carried out the dental examinations at different times during the study period, making inter-observer variability a limitation of the study, especially in the detection of caries and the grading of oral and denture hygiene.…”
Section: Discussionmentioning
confidence: 99%